ISOLATED SYSTOLIC HYPERTENSION AND RISKS OF STROKE IN THE OLDEST OLD - Kheirbek, R (Innov Aging, 2018)
Aim With nearly 800,000 Americans suffering from stroke each year, it became a leading cause of death. Hypertension is the chief culprit, yet optimal blood pressure for the oldest old remains controversial. We investigated the association hypertension and stroke risk in an oldest old. Methods The study included 86,892 community-dwelling veterans born between 1910 - 1915 survived to at least age 80. Retrospective longitudinal cohort study. Data from the Department of Veterans Affairs (VA) Informatics and Computing Infrastructure were used. Kaplan–Meier method estimated cumulative incidence of stroke in the two groups (those with hypertension and those without hypertension) and compared using the log-rank test. Cox proportional hazards models were used to estimate unadjusted hazard ratios. We estimated hypertension onset age by calculating the time difference between date of diagnosis and date of birth Results Ninety-seven percent of subjects were male, 88.0% were white, 31.8% were widowed, 87.5% served in World War II, and 63.9% did not have a service- related disability However, higher SBP was not associated with an increased incident stroke in patients with SBP less than 150 mmHg (hazard ratio 0.87, 95% CI 0.53–1.53). Patients over 90 with a new onset of hypertension had the lowest risk (HR=0.37, p=0.004). CONCLUSION: In a large cohort of predominantly male community-dwelling elderly veterans, developing hypertension at older ages may protect against stroke. Further studies are needed to evaluate mechanism for this lower risk in order to determine ways to prevent strokes in the oldest old.